LIVING LIFE - Paulus, Andre; Pramuditha, Charisma Ayu (Universitas Multi Data Palembang, 2023)
Living Life is a business engaged in the service sector that provides household assistants. This business offers household assistants with 3 options in the application, namely helpers, security guards, and drivers. This business is located at Jalan Aiptu Karel Satsuit Tubun No. 856, RT.12/RW.04, 17 Ilir, Kec. Team Ilir. 1, Palembang City, South Sumatra 20125. The establishment plan is focused on product concept innovation. Business feasibility analysis is carried out using 3 analytical methods, namely financial statement analysis, feasibility analysis, and business profit analysis. The promotion will be carried out using online media and brochures. Based on the business feasibility aspect, Living Life is declared feasible to run and has profitable prospects in the future.